Mathematics - Rohana Ismail; Lee Beng Hin; Affaf Mohamad Md Yusoff (Effective practice for matriculation, 2018)
This book is for matriculation semester 2 which is written for students studying mathematics in local matriculation courses. This revision book aims to give students a comprehensive coverage of the type of questions they may encounter in their matriculation examinations.